Research alone is not sufficient to prevent sports injury - Hanson, Dale; Allegrante, John P; Sleet, David A; Finch, Caroline F (British journal of sports medicine, 2014)
Unless this research culminates in practical and cost-effective interventions capable of attracting the political and social support required to allow effective implementation, it will not prevent harm or save lives. 1 The Public Health Model has been proposed as a framework to promote the progression of sports medicine research towards real-world application. 2 3 In this four-stage model, research progresses in a stepwise manner from problem identification to adoption of effective interventions: 4 Stage 1: establishing the magnitude of the problem; Stage 2: identifying risk factors; Stage 3: developing effective interventions; Stage 4: ensuring widespread adoption and use. Contrary to Mercy et al's 3 advice, some researchers adopted a top-down approach, believing that Stages 1-3 of the Public Health Model are the province of scientific experts, while Stage 4 (dissemination, implementation and adoption) was the domain of community practitioners who were expected to take efficacious interventions and faithfully apply them to improve practice. 21 This science-driven misapplication of the Public Health Model ignores the importance of engaging practitioners, policy makers and the community in the process of designing, researching and implementing effective interventions, falsely assuming that efficacious interventions can be automatically adopted and effectively implemented at a population level. 6 9 16 Researchers who ignore the contextual, implementation and process determinants of intervention success should not be surprised if practitioners and the community are unwilling or unable to adopt evidence-based interventions to prevent sports injury. 6 9 In the intense discourse between researchers and practitioners it is easy to forget a third group of stakeholders-the community.